Variability in Seed Traits in a Collection of Cannabis sativa L. Genotypes - Galasso, Incoronata; Russo, Roberto; Mapelli, Sergio; Ponzoni, Elena; Brambilla, Ida M.; Battelli, Giovanna; Reggiani, Remo (Frontiers in Plant Science, 2016)
Hempseed could be a new source of proteins and oil for both humans and animals. In this study, the proximate composition of a collection of hempseed cultivars and accessions of different geographical origins grown under the same conditions was analyzed. Fatty acids, tocopherols and antinutritional components, as well as concentrations of crude protein and oil were quantified. Hempseed oil concentrations varied between 285 and 360 g kg-1 dry seed (DS), while crude protein ranged between 316 and 356 g kg-1 dry matter (DM). The hempseed oil was mainly composed of unsaturated fatty acids and, as expected, the dominant fatty acids were linoleic and α-linolenic acid. A high variability among the cultivars and accessions was also detected for polyphenolic content which ranged from 5.88 to 10.63 g kg-1 DM, cv. Felina was the richest, whereas cv. Finola had the lowest polyphenolic content. Regarding antinutritional compounds in seed, a high variability was detected among all genotypes analyzed and phytic acid was particularly abundant (ranging between 43 and 75 g kg-1 DM). In conclusion, our results reveal noticeable differences among hempseed genotypes for antinutritional components, oil and protein content. Collectively, this study suggests that the hempseed is an interesting product in terms of protein, oil and antioxidant molecules but a reduction of phytic acid would be desirable for both humans and monogastric animals. The high variability detected among the different genotypes indicates that an improvement of hempseed might be possible by conventional and/or molecular breeding.